Línea de base del proyecto de salud sexual y reproductiva para adolescentes en Medellín: componente cualitativo (2009)
ABSTRACT: To approach the perception of adolescents and adults opinion makers on teenage pregnancy, sexual and reproductive health (srh), use of birth control (bc) and use of srh services. Methodology: a descriptive study ethnographic with focused interviews and semi-structured guide. The convenience sample consisted of 80 young people (men and women) between 14 and 19 years old and 6 adult women opinion makers. Eight focus groups were conducted with youth and six interviews. Results: in intergenerational encounters are explanatory reasons on teenage pregnancy in the city of Medellin The construction of the process of trust-distrust in the conquest and the adolescent partner life affects the use of bc, including the condom. The main barrier to adolescents’ access to srh services is the lack of credibility in them. Conclusions: The break with the ideal of the adult world, the ideas they have about love, relationships, cultural precepts that designate the gender behavior and credibility they have about srh services are fields of analysis that are directly linked to the issue of teenage pregnancy in the city of Medellin.